External assessment form for private optometry premise industrial training, Bachelor of Optometry (Honours), International Islamic University Malaysia - Md Mustafa, Md Muziman Syah; Hilmi, Mohd Radzi (2020)
External assessment form for private optometry premise industrial training is developed as a tool to evaluate the clinical performance and communication skills of optometry students during industrial training at the private optometry premise. The form will be provided to the respective external assessors at private optometry premises.